25th AIAA/AHS Adaptive Structures Conference 2017
DOI: 10.2514/6.2017-0731
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Strain Constitutive Model for Martensitic Transformation in Shape Memory Alloys Based on Logarithmic Strain

Abstract: Shape Memory Alloys (SMAs) are materials with the ability to recover apparently permanent deformation under specific thermomechanical loading. The majority of constitutive models for SMAs are developed based on the infinitesimal strain theory. However, such assumption may not be proper in the presence of geometric discontinuities, such as cracks, and repeated cycling loading that has been reported to induce irrecoverable strains up to 20% due to transformation induced plasticity. In addition to finite strains,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Implementing various constitutive models [7][8][9][10][11], fracture of SMAs has been studied numerically in the presence of stationary cracks [12][13][14][15][16][17][18][19]. It is shown that stress concentration at the crack tip causes forward transformation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Implementing various constitutive models [7][8][9][10][11], fracture of SMAs has been studied numerically in the presence of stationary cracks [12][13][14][15][16][17][18][19]. It is shown that stress concentration at the crack tip causes forward transformation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a lot of constitutive modeling efforts been made during recent decades to predict the intrinsic material response of SMAs, a through review can be found from elsewhere. [24][25][26][27] As the motivation of this research is to facilitate the development of a phenomenological model that is able to capture the tensioncompression asymmetry and TRIP during cyclic thermo-mechanical actuation loading, the results obtained from previously performed tension/compression and bending experiments are used for the formulation and validation of the SMA constitutive model capturing the anisotropic phase transformation characteristics. In order to achieve the desired modeling capability, modifications on the transformation functions are needed.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…A three-dimensional constitutive model at finite strain regime for SMAs incorporating TRIP is proposed in this work. The adopted logarithmic strain measure and rate [20,21,22,23] enables the model to effectively capture the material response under finite strains with rotations, and attribute modeling advantages in the presence of large accumulated plastic strain under cyclic thermo-mechanical loading for SMAs. The martensitic volume fraction, transformation strain, and TRIP strain are used to characterize material nonlinear behavior while back stress tensor and a drag stress term are used to introduce the effects of the kinematic and isotropic hardening in the model.…”
Section: Introductionmentioning
confidence: 99%